Deciphering Innate Immune Cell-Tumor Microenvironment Crosstalk at a Single-Cell Level - Sugimura, Ryohichi; Chao, Yiming (Frontiers in Cell and Developmental Biology, 2022)
This review addresses the update of scRNA-seq that advances the understanding of TME. We have listed publicly available dataset and useful codes, so each informatician can do data-mining.